ENVIRONMENTAL NEGLECT AND RESPONSIBILITY IN ELEMENTARY CLASSROOMS: A DESCRIPTIVE QUALITATIVE STUDY USING SOCRATIC-ORIENTED QUESTIONNAIRES - Emma Maryam Andrew; Paula Coa Christenia Mekar Kusuma Maharani (Jurnal Cakrawala Pendas, 2026)
Environmental responsibility in elementary schools is often promoted through rules, reminders, and routines. Yet students may still ignore visible problems, such as litter, misplaced belongings, and untidy classrooms, even when they know cleanliness matters. This study examines environmental neglect as a gap between awareness and responsible action in everyday classroom life. Using a descriptive qualitative design, data were collected from 20 elementary students and one teacher at Cendekia Harapan School, Bali, through an online open-ended questionnaire with Socratic-oriented reflective questions about responsibility, consequences, and action. Data were analyzed thematically, with simple percentages used only to describe one closed-response item. The findings show that environmental neglect is shaped by weak personal responsibility, limited awareness of consequences, dependence on teacher reminders, reluctance to act, and peer influence. These themes indicate that environmental neglect is not merely a knowledge problem, but a reflective responsibility gap. The study contributes to environmental character education by showing the need to combine reflective questioning, teacher modeling, classroom routines, and shared responsibility to help students transform environmental awareness into consistent action.